2010
DOI: 10.1016/j.carbpol.2010.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel structure in heparin generated by potassium permanganate oxidation

Abstract: The worldwide heparin contamination crisis in 2008 led health authorities to take fundamental steps to better control heparin manufacture, including implementing appropriate analytical and bio-analytical methods to ensure production and release of high quality heparin sodium product. Consequently, there is an increased interest in the identification and structural elucidation of unusually modified structures that may be present in heparin. Our study focuses on the structural elucidation of species that give ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…In addition, both depolymerization processes lead to the opening of a proportion of the reducing GalNAc ring and formation of the galactosaminic acid by further oxidation, as evidenced also by the additional oxygen identified by MS ( Fig. 3 ), similar to glucosaminic acid in heparin depolymerization reported previously ( 64 , 65 ). Albeit heterogeneous, these oligosaccharides were considered suitable for initial selectin binding studies.…”
Section: Resultssupporting
confidence: 76%
“…In addition, both depolymerization processes lead to the opening of a proportion of the reducing GalNAc ring and formation of the galactosaminic acid by further oxidation, as evidenced also by the additional oxygen identified by MS ( Fig. 3 ), similar to glucosaminic acid in heparin depolymerization reported previously ( 64 , 65 ). Albeit heterogeneous, these oligosaccharides were considered suitable for initial selectin binding studies.…”
Section: Resultssupporting
confidence: 76%
“…In 2000, internal studies on Lovenox coloration revealed that the modification of the heparin purification process impacts the heparin linkage region and generates distinct heparin process signatures [18]. For example, potassium permanganate, which is mainly used as an oxidizing agent to remove the glycoserine linkage sequence from the polysaccharide, also in addition generates the 2.10 ppm NMR signal [12,13]. Chromatographic analysis of exhaustive heparinase digests shows that heparins from the ES source have also almost totally lost their serine ends in an oxidative process giving a "chromatographic signature" different from that of EV source-heparins.…”
Section: Resultsmentioning
confidence: 99%
“…Additional techniques such as Strong Anion Exchange chromatography [7] or capillary electrophoresis [8,9] were extensively explored. Our laboratory is experienced in the isolation of pure oligosaccharides from various heparinoids [10,11] and has previously identified the structural moiety responsible for an extra signal at 2.10 ppm observed in the 1 H NMR spectra of potassium permanganate-treated heparins [12,13]. This extra signal could have caused compliance issues for these heparins; however, when the source was characterized, the signal was shown to be due to oxidation of the aldehyde at the reducing end and ultimately traced not to a contaminant of heparin, but to the use of potassium permanganate in the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Signals of N-acetyl galactosamine of CS are observed at 2.02 ppm, while that of DS is at 2.08 ppm. On the other hand, GlcNAc signals of HS are detected at 2.04 and 2.06 ppm, while those of oxidized N-acetyl hexosamine (ANAc-ox) are at 2.1 ppm ( Figure 2 b) [ 16 , 17 , 18 ]. A comparison between acetyl regions of different samples is reported in Figure S1 .…”
Section: Resultsmentioning
confidence: 99%